Chapter Dal sogno alla realtà. Spunti di autobiografia intellettuale in Gerolamo - Gamberale, Leopoldo (Firenze University Press, 2025)
This contribution analyzes several passages, especially from Jerome’s epistles, from which it emerges that the Father includes autobiographical informations in a context of literary and cultural elaboration; and, in addition, he changes it according to the occasion, the type of letter, the recipient. It is not a question of falsification, but precisely of intellectual elaboration, a kind of ‘construction of himself’ variously adapted by Jerome over the course of his life